IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DALAM PEMBENTUKAN KARAKTER DI SEKOLAH DASAR INKLUSI - Sarjono, Meyra Tri; Zakiah, Linda; Saputra, Marcelino Adi; Hendrick, Ziva Trevina; Maulidina, Citra Ashri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Multicultural education is an educational approach that values and recognizes the diversity of students' cultures, backgrounds, and identities. Implementing multicultural education in inclusive primary schools can contribute to building inclusive, tolerant, and respectful attitudes toward differences in students. This research uses qualitative research methods, while the data collection technique is through a literature study. The results showed that implementing multicultural education in student character building can be done through Ki Hadjar Dewantara's tricentric education concept, religious learning, civic education, and integration with other subjects. This implementation has a positive influence on student character, including increased understanding and appreciation of differences, the formation of tolerance and mutual respect, improved communication skills, increased teamwork and problem-solving, and increased awareness.